Performance-Based Strategy on Evaluating to Write for Student at Arabic Literature Faculty of Universitas Negeri Malang - Luthfi Abdul Manaf (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Purpose - This study aims to uncover the Performance-Based Strategy on Evaluating to Write for students at the Arabic Literature Faculty of Universitas Negeri Malang. Design/methodology/approach - This research uses a qualitative approach with a multi-site case study type. While the primary data collection method uses in-depth interviews, and the secondary data uses the Participant Observation and Documentation methods. Findings - This study reveals the Performance-based strategy used by lecturers in writing: writing simple sentences and compound sentences and writing descriptions of places and things. Originality/value - The Use of a Performance-based strategy can help the teacher obtain accurate information in determining learning outcomes in learning to write. Paper type – Research Paper